Does BCR/ABL1 positive Acute Myeloid Leukaemia Exist?. (25th March 2013) - Nacheva, Ellie P.; Grace, Colin D.; Brazma, Diana; Gancheva, Katya; Howard‐Reeves, Julie; Rai, Lena; Gale, Rosemary E.; Linch, David C.; Hills, Robert K.; Russell, Nigel; Burnett, Alan K.; Kottaridis, Panagiotis D.
Summary The BCR/ABL1 fusion gene, usually carried by the Philadelphia chromosome (Ph) resulting from t(9;22)(q34;q11) or variants, is pathognomonic for chronic myeloid leukaemia (CML). It is also occasionally found in acute lymphoblastic leukaemia (ALL) mostly in adults and rarely in de novo acute myeloid leukaemia (AML). Array Comparative Genomic Hybridization (aCGH) was used to study six Ph(+)AML, three bi‐lineage and four Ph(+)ALL searching for specific genomic profiles. Surprisingly, loss of the IKZF1 and/or CDKN2A genes, the hallmark of Ph(+)ALL, were recurrent findings in Ph(+)AML and accompanied cryptic deletions within the immunoglobulin and T cell receptor genes. The latter two losses have been shown to be part of 'hot spot' genome imbalances associated with BCR/ABL1 positive pre‐B lymphoid phenotype in CML and Ph(+)ALL. We applied Significance Analysis of Microarrays (SAM) to data from the 'hot spot' regions to the Ph(+)AML and a further 40 BCR/ABL1(+) samples looking for differentiating features. After exclusion of the most dominant markers, SAM identified aberrations unique to de novo Ph(+)AML that involved relevant genes. While the biological and clinical significance of this specific genome signature remains to be uncovered, the unique loss within the immunoglobulin genes provides a simple test to enable the differentiation of clinically similar de novo Ph(+) AML and myeloid blast crisis of CML.